A relação entre cultura e bem-estar subjetivo em perspectiva comparativa: evidências a partir do individualismo-coletivismo. - Barroso, Luiz Felipe Oliveira (Universidade Federal de São Carlos, 2022)
The use of self-reported measures of well-being, including the degree of satisfaction with life, allowed a series of new assessments of well-being, previously limited to objective indicators. The study of the literature built on these subjective measures identified patterns in the effects of economic and sociodemographic characteristics on the degree of satisfaction of individuals. In a step forward, with the adoption of international databases, these effects began to be evaluated at the national level. The results of these analyzes indicated differences in the level of satisfaction in different countries, justified only partially by economic characteristics. The objective of this work is to identify whether cultural characteristics influence the degree of satisfaction declared in different countries, through a traditional model of determinants of subjective well-being. The methodological differential of this research is the strategy adopted in two stages, incorporating cultural dimensions, centered on the continuous individualism-collectivism, and the estimation of a hierarchical econometric model for the levels of satisfaction with life. The first step of this strategy is the construction of the cultural dimension of individualism, through behavioral questions included in the World Values Survey (Waves 5 and 6), reduced to an index using the Multiple Correspondence Analysis method. The results of this section compared to the literature on cultural values indicate convergences, such as Sinic Asia countries showing a lower level of individualism in the sample, and divergences, with countries from the New West and Protestant Europe groups also aligned close to the collectivist limit of the cultural continuum, which would not theoretically be expected. In the second step, this index is included in a multilevel econometric model, interacting with regional dummys, which makes it possible to find some significant, albeit discrete, effects on the declared level of satisfaction. This approach found negative impacts of individualism in Indian Asia, Islamic East, Sub-Saharan Africa groups, and positive effects of individualism on the average satisfaction level in Protestant Europe and Latin America groups, compared to the median cultural group. These results indicate some adherence to the hypothesis that satisfaction levels are affected by cultural values, even if they are limited to the mentioned groups of countries. Finally, the limits of this type of approach are also discussed, from the validity of the measures and the database used, as well as possible alternatives in future investigations involving subjective well-being and culture.
The relationship between culture and subjective well-being in a comparative perspective: evidence from individualism-collectivism.
Keywords: Economia da felicidade; Bem-estar subjetivo; Cultura e bem-estar; Happiness economics; Subjective well-being; Culture and well-being; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::TEORIA ECONOMICA